Increasing Rice Yield through Targeting Genetic Potentials by Rice Types (Bangladesh Rice Journal, 2021)
Bangladesh needs an average rough rice yield of 9.11 t ha-1 by 2050 which can not be achieved equally across all the geographic regions since the country has various ‘rice types’ with varying yield potentials. This paper focuses on strategic innovations for reaching the yield target by refining rice types. Based on rice ecosystems and the pressing needs, we divided rice areas of Bangladesh in 17 different types. We estimated year-wise land areas and allocated achievable yield targets for each of the rice types. Finally, we compared the target yields and the yields of top-yielding rice varieties in Bangladesh by 2020 across the rice types to understand the current status of our varietal improvement programmes. We sorted out how much improvement is needed in each rice types. Among the rice types, cold-tolerant (Northern and Western) was sorted out as the most potential area of rice yield improvement where rice varieties will be released having a yield advantage of 4.04 t ha-1 by 2050. The chronology of next priority areas for high yielding variety development and their target yield advantages in t ha-1 are saline Boro (4.03), Favourable Boro (long duration) (4), cold-tolerant (Haor) (3.83), tidal submergence (3.8), Healthier rice (Boro) (3.58), Favourable Boro (short duration) (3.33), Healthier rice (Aman) (3.3), Favourable Aman (3.23), Flash flood (3.09), upland rice (2.89), Saline Aman (2.8), Healthier rice (Aus) (2.53), Premium quality rice (2.53), drought (2.38), T. Aus (2.05) and deepwater. Combined genetic interventions like population improvement through cyclic breeding, genomic selection, marker-assisted selection, genome editing, genetic transformation, germplasm utilization through genome-wide association study and phenomics, and development of super hybrid rice are being used in the country to attain yield target for different rice types.Bangladesh Rice J. 24 (2): 67-82, 2021